Genome wide association study of growth and feed efficiency traits in rabbits - Hervé Garreau; Yann Labrune; Hervé Chapuis; Julien Ruesche; Juliette Riquet; Julie Demars; Florence Benitez; François Richard; Laurence Drouilhet; Olivier Zemb; Hélène Gilbert (World Rabbit Science, 2023)
Feed efficiency is a major production trait in animal genetic breeding schemes. To further investigate the genetic control of feed efficiency in rabbits, we performed a genome-wide association study (GWAS) for growth and feed efficiency on 679 rabbits genotyped with the Affimetrix Axiom Rabbit 200K Genotyping Array. After quality control, 127 847 single-nucleotide polymorphisms (SNP) were retained for association analyses. The GWAS were performed using GEMMA software, applying a mixed univariate animal model with a linear regression on each SNP allele. The traits analysed were weight at weaning and at 63 days of age, average daily gain, total individual feed intake, feed conversion ratio and residual feed intake. No significant SNP was found for growth traits or feed intake. Fifteen genome-wide significant SNPs were detected for feed conversion ratio on OCU7, spanning from 124.8 Mbp to 126.3 Mbp, plus two isolated SNP on OCU2 (77.3 Mbp) and OCU8 (16.5 Mbp). For residual feed intake, a region on OCU18 (46.1-53.0 Mbp) was detected, which contained a putative functional candidate gene, GOT1.